2020
DOI: 10.3390/biom10040497
|View full text |Cite
|
Sign up to set email alerts
|

CSF Ubiquitin Levels Are Higher in Alzheimer’s Disease than in Frontotemporal Dementia and Reflect the Molecular Subtype in Prion Disease

Abstract: Disturbances in the ubiquitin-proteasome system seem to play a role in neurodegenerative dementias (NDs). Previous studies documented an increase of cerebrospinal fluid (CSF) free monoubiquitin in Alzheimer’s disease (AD) and Creutzfeldt–Jakob disease (CJD). However, to date, no study explored this biomarker across the heterogeneous spectrum of prion disease. Using a liquid chromatography−multiple reaction monitoring mass spectrometry, we investigated CSF free monoubiquitin in controls (n = 28) and in cases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…Many of these markers are universal across NDDs, supporting the idea of a common neuroinflammatory profile across these diseases. Some of these common neuroinflammation mediators are chitotriosidase 1 (CHIT1), chitinase-3-like protein 1 (YKL-40), the glial fibrillary acidic protein (GFAP) and important pro-inflammatory cytokines, such as interleukin-1β (IL-1), IL-6 and tumor necrosis factor α (TNF-α) [ 41 , 42 ].…”
Section: Neuroinflammation As a Common Factor Across Neurodegeneramentioning
confidence: 99%
“…Many of these markers are universal across NDDs, supporting the idea of a common neuroinflammatory profile across these diseases. Some of these common neuroinflammation mediators are chitotriosidase 1 (CHIT1), chitinase-3-like protein 1 (YKL-40), the glial fibrillary acidic protein (GFAP) and important pro-inflammatory cytokines, such as interleukin-1β (IL-1), IL-6 and tumor necrosis factor α (TNF-α) [ 41 , 42 ].…”
Section: Neuroinflammation As a Common Factor Across Neurodegeneramentioning
confidence: 99%
“…Demographic and clinical data of the sCJD cohort are shown in Supplementary Table S3. For the analysis according to the sCJD molecular subtypes, we merged the subjects with definite sCJD (28 MM(V)1, 15 VV2 and 13 MV2K) with those with a probable sCJD diagnosis (five VV2 and two MV2K) and a high level of certainty for a given subtype as described [22]. In each case, we calculated the length of survival and the disease stage as described [23].…”
Section: Patient Selection Csf and Neuropathological Analysesmentioning
confidence: 99%
“…In each case, we calculated the length of survival and the disease stage as described [23]. The control group included 25 subjects lacking any clinical or neuroradiologic evidence of central nervous system disease and having CSF p-tau, t-tau and Aβ42 in the normal range [22].…”
Section: Patient Selection Csf and Neuropathological Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been speculated that neurogranin levels could be useful to differentiate between different subtypes of CJD (different concentrations having reported according to the clinicopathological subtypes) [4]. Interestingly, it has been reported that ubiquitin, which marks neuritic damage, dysfunctional protostasis and neuroinflammation, has higher concentrations in CJD than in controls and other neurodegenerative dementias, and especially in less frequent forms of sCJD such as MM(V)1 [64,65]. One study has also shown higher levels of calmodulin, a ubiquitous calcium-binding protein, in sCJD compared to other neurodegenerative dementias particularly in those with higher levels of t-tau [66].…”
Section: Other Biomarkersmentioning
confidence: 99%